The importance of education for humans - Ahmad Zuhdi; Firman Firman; Riska Ahmad (SCHOULID: Indonesian Journal of School Counseling, 2021)
Humans are intelligent creatures and are endowed with various abilities. In essence, humans are creatures that have two roles, namely as individual beings and also as social beings. Humans are individual beings consisting of physical and spiritual elements created by God which cannot be separated. To achieve human nature as intelligent beings, education is needed. Education means an effort to develop the innate potential both physically and spiritually in humans according to the values that exist in society and culture. Therefore, researchers conducted a literature review on humans and education. The research method uses literature study. The research findings reveal that between humans and education is an inseparable unity.